2011
DOI: 10.1073/pnas.1010744108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of active mutant L858R EGF receptor (EGFR) kinase-expressing nonsmall cell lung carcinomas using PET/CT

Abstract: The importance of the EGF receptor (EGFR) signaling pathway in the development and progression of nonsmall cell lung carcinomas (NSCLC) is widely recognized. Gene sequencing studies revealed that a majority of tumors responding to EGFR kinase inhibitors harbor activating mutations in the EGFR kinase domain. This underscores the need for novel biomarkers and diagnostic imaging approaches to identify patients who may benefit from particular therapeutic agents and approaches with improved efficacy and safety prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 64 publications
2
71
0
Order By: Relevance
“…A newer version of this probe, [ 18 F]F-PEG6-IPQA, which has better water solubility, has also been developed. [ 18 F]F-PEG6-IPQA could detect NSCLC xenograft tumors harboring L858R activating EGFR mutations, and did not recognize NSCLC xenografts expressing either wild type or L858R/T790M dual mutant EGFR (Yeh et al, 2011). Another irreversible TKI analog ML04 exhibited excellent specificity to EGFR in vitro.…”
Section: Tki Derivativesmentioning
confidence: 99%
“…A newer version of this probe, [ 18 F]F-PEG6-IPQA, which has better water solubility, has also been developed. [ 18 F]F-PEG6-IPQA could detect NSCLC xenograft tumors harboring L858R activating EGFR mutations, and did not recognize NSCLC xenografts expressing either wild type or L858R/T790M dual mutant EGFR (Yeh et al, 2011). Another irreversible TKI analog ML04 exhibited excellent specificity to EGFR in vitro.…”
Section: Tki Derivativesmentioning
confidence: 99%
“…As expected, gefitinib treatment did not affect the drug-resistant tumor cells, H441, which had F]F-PEG6-IPQA uptake was also decreased in H1975 and PC14 tumor xenograft models. H1975 cells have the L858R mutation, which is sensitive to gefitinib, but they also have second mutation, T790M, which gives resistance to gefitinib by interfering its binding to the ATP binding site of EGFR kinase (Yeh et al, 2011). This tracer may allow detection of EGFR-positive tumors expressing L858R mutation and help distinguish patients who will respond to EGFR-TK inhibitors such as gefitinib and erlotinib.…”
Section: A Sustaining Proliferative Signalingmentioning
confidence: 99%
“…Another study reported by Yeh et al (2011) described the preclinical study of small molecule TK-inhibitor, [ and to less degree in genfitinib-resistant H441 tumors (1.59 6 0.44%ID/g), whereas uptake in H1975 and PC14 tumors was low and similar to muscle background (Yeh et al, 2011). [ 18 F]F-PEG6-IPQA uptake was significantly reduced after treatment with gefitinib (1.38 6 0.43%ID/g) in H3255 tumors.…”
Section: A Sustaining Proliferative Signalingmentioning
confidence: 99%
“…A notable exception is the recent development of 18 F-PEG 6 -IPQA, which, in addition to measuring target density and distribution, binds irreversibly with high selectivity to activated mutant L858R epidermal growth-factor receptor in non-small cell lung carcinoma. Thus, 18 F-PEG 6 -IPQA can potentially be used to predict response or resistance to gefitinib or erlotinib treatment (9).…”
Section: Biomarker Classificationmentioning
confidence: 99%